One- and two-dimensional liquid chromatographic methods hyphenated to ion mobility spectrometry – high resolution mass spectrometry for the detailed characterisation of industrial wood tannin extracts - Crowder, James (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2023.